2016
DOI: 10.5424/sjar/2016143-8951
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and antioxidant activities of grape canes extracts from vineyards

Abstract: matic, and natural or synthetic sources (Nardini et al., 2005). Natural phenolics possess strong antioxidant properties that enable them to donate hydrogen, scavenge free radicals, break radical chain reactions, chelate metal ions, and quench singlet oxygen in vitro and in vivo (Rice-Evan et al., 1996).Previous studies have revealed that one-third of all cancer cases and one-half of cardiovascular diseases RESEARCH ARTICLE OPEN ACCESS AbstractGrape canes are the main agro-wastes from vineyards. This work stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The radical-scavenger capacity ranged from 15 (TPS/WE5) to 39% (TPS/WE15) using water as a solvent, from 38 to 87 in methanol/water 80/20 v/v, and from 31 to 86% in absolute methanol, for 1000 µL of DPPH solution. High antioxidant capacity of obtained grape cane extract has been already proven in our previous paper [26] and supported in the literature by other authors [45,46], due to the presence of phenolic groups in extract itself. The IC 50 (concentration required to scavenge 50% DPPH radicals) values of the oligostillbenes caraphenol A and α-viniferin A were determined and compared with Trolox antioxidant standard by Li et al [47].…”
Section: Antioxidant Capacitysupporting
confidence: 83%
“…The radical-scavenger capacity ranged from 15 (TPS/WE5) to 39% (TPS/WE15) using water as a solvent, from 38 to 87 in methanol/water 80/20 v/v, and from 31 to 86% in absolute methanol, for 1000 µL of DPPH solution. High antioxidant capacity of obtained grape cane extract has been already proven in our previous paper [26] and supported in the literature by other authors [45,46], due to the presence of phenolic groups in extract itself. The IC 50 (concentration required to scavenge 50% DPPH radicals) values of the oligostillbenes caraphenol A and α-viniferin A were determined and compared with Trolox antioxidant standard by Li et al [47].…”
Section: Antioxidant Capacitysupporting
confidence: 83%
“…ABTS radical scavenging activity of the wine sample was performed according to the published methods with minor modifications [ 15 , 32 ]. Briefly, 7 mM ABTS solution was mixed with 140 mM potassium persulfate aqueous solution to generate ABTS radical cation.…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic compounds have been reported to have capacity of scavenging free radicals, donating hydrogen, chelating metal ions, breaking radical chain reaction, and quenching singlet oxygen [ 15 ]. It has been also suggested that phenolic compounds could enhance the endogenous antioxidant capacity of cells/tissues and interact with cellular receptors and/or enzymes, which could improve human health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations